TRANSFORMATION STUDIES OF CAFFEINE DEGRADING PLASMID FROM BREVIBACTERIUM SPECIES - SUMITHA.J (International Journal of Pharma and Bio Sciences, 2014)
The study of caffeine degrading plasmid from Brevibacterium, isolated and maintained in our laboratory from the coffee samples obtained from West Karnataka was undertaken.A plasmid of about 2000 bp was isolated from Brevibacterium . The isolated plasmid was used to transform Escherichia coli DH5α and the transformed colonies were inoculated in 1 to 10 g/L of caffeine containing minimal media to investigate whether the plasmid was involved in biodegradation of caffeine. It was observed that the plasmid biodegraded caffeine up to 8 g/L in minimal media, whereas non-transformed colonies could tolerate only up to 1 g/L caffeine. Growth curves obtained in the minimal media showed that transformed cells of Escherichia coli DH5α have greater ability to tolerate and degrade caffeine as compared to non-transformed cells.